Vortioxetine Prevents Lipopolysaccharide-Induced Memory Impairment Without Inhibiting the Initial Inflammatory Cascade - Alboni, S.; Benatti, C.; Colliva, C.; Radighieri, G.; Blom, J. M. C.; Brunello, N.; Tascedda, F. (Frontiers in Pharmacology, 2021)
Vortioxetine is a novel multimodal antidepressant which modulates a wide range of neurotransmitters thought the brain. Pre-clinical and clinical studies have shown that vortioxetine exerts positive effects in different cognitive domains as well as neuroprotective effects. Considering the key role of microglia cells in brain plasticity and cognition, we aimed at investigating the effects of a pretreatment with vortioxetine in modulating behavioral and molecular effects induced by an immune challenge: peripheral injection of liposaccharide (LPS). To this purpose, C57BL/6J male mice were exposed first to 28 days of a standard diet or a vortioxetine enriched diet, which was followed by an acute immune challenge with LPS. Sickness symptoms and depressive like behaviors (anhedonia and memory impairment), were tested respectively 6 and 24 hours after exposure to LPS. Moreover, the expression of markers of immune activation and M1/M2 markers of microglia polarization was measured in the dorsal and ventral parts of the hippocampus. The pre-treatment with vortioxetine did not affect both LPS-induced sickness behavior and anhedonia but prevented the deficit in the recognition memory induced by the immune challenge. At the transcriptional level chronic exposure to vortioxetine did not prevent LPS-induced upregulation of proinflammatory cytokines 6 hours after the immune challenge, but rather seemed to potentiate the immune response to the challenge also by affecting the levels of expression of marker of microglia M1 phenotype, like cluster of differentiation (CD)14 and CD86, in an area dependent manner. However, at the same time point, LPS injection significantly increased the expression of the M2 polarization inducer, interleukin 4, only in the hippocampus of animals chronically exposed to vortioxetine. These results demonstrate that a chronic administration of vortioxetine specifically prevents LPS-induced memory impairment, without affecting acute sickness behavior as well as anhedonia, and suggest that hippocampal microglia may represent a cellular target of this novel antidepressant medication. Moreover, we provide a useful model to further explore the molecular mechanisms specifically underlying cognitive impairments following an immune challenge.